Pretrial justice reform and property crime: Evidence from New Jersey - KIM, Jung K. (Institutional Knowledge at Singapore Management University, 2020)
Several states and localities have begun to implement various forms of pretrial justice reforms aimed at reducing the size of pretrial detainee population. However, empirical investigation of the effect of such reforms on crimes more broadly (other than recidivism) is limited. We analyse the effect of the 2017 New Jersey Criminal Justice Reform on property crimes. We find that property crime per 100,000 population increased by 22.5% within the first two years. Our findings suggest that reducing the likelihood of pretrial detention for less violent crimes can have substantial impact on behavioural incentives for offenders of such crimes.